An optimal method of distribution of the slip zone on thrust bearing surfaces. (June 2022) - Wu, Zhenpeng; Nguyen, Vanliem; Dong, Bowen; Ke, Chao; Guo, Xiaoyan; Zeng, Liangcai
Research to achieve a reasonable distribution of the slip zone of the sliding pair for better improvement of the hydrodynamic pressure of the liquid film is an intractable topic. To solve this issue, this paper takes the thrust bearing as the research object, and proposes to use the position number of the grid nodes at the boundary line between the slip and no-slip zone in each radial zone of the inclined pad to be variables. The variables are then defined as chromosomes in an adaptive genetic algorithm (AGA) and used to optimize the bearing capacity of the tilting pad. The results show that the optimal method of the AGA, which has good stability and repeatability, remarkably improves the distribution of the slip zone on the surface of the inclined pad. Therefore, the bearing capacity of the liquid film is significantly improved. Particularly, by using the optimization, the boundary line between the slip/no-slip zone is a composite form of a part of an arc and a part of the whisker. When the liquid flow through the heterogeneous slip/on-slip surfaces is used by this composite splicing method, the liquid pressure is upgraded in two steps. This is more conducive to increasing the pressure on multiple areas on the surface of the tilting pad, thereby achieving higher bearing capacity.